The Relationship Between Promotion and Prevention Regulatory Focus and Job Crafting: The Mediating Role of Career Decision Ambiguity Tolerance - Kabzińska, Zofia (Przegląd Psychologiczny, 2025)
Objective: The aim of the study was to identify individual predictors of job crafting, understood as the proactive efforts of employees to modify aspects of their work. Job crafting refers to bottom-up initiatives undertaken by employees to adjust their job roles to better fit their skills, needs, and preferences. According to the adopted theoretical model, these initiatives encompass three domains: task crafting, relational crafting, and cognitive crafting. Method: The study involved 558 employed individuals aged 18 to 76 years (M = 40.1, SD = 11.7). The following instruments were used to measure the variables: the Job Crafting Questionnaire by Slemp & Vella-Brodrick, adapted by Kasprzak et al.; the Regulatory Focus Scale (promotion and prevention) by Kolańczyk, Bąk, and Brzezińska; and the Career Decision Ambiguity Tolerance Questionnaire by Xu and Tracey. Results: Promotion focus, prevention focus, and motivational strength emerged as predictors of both tolerance of ambiguity and job crafting in the tested mediation models. The results also confirmed the presence of indirect effects of promotion focus, prevention focus, and motivational strength on job crafting through the mediator—ambiguity tolerance. Conclusion: The findings contribute to a better understanding of the individual factors that facilitate job crafting. They also suggest that strengthening employees’ personal resources may support effective job crafting within organizations.